Education to maintain dental health for children at SDIT Al-Madinah Bogor - Melaniwati Melaniwati; Wiwiek Poedjiastuti; Raden Roro Asyurati Asia; Muhammad Ihsan Rizal; Lia Hapsari Andayani; Florencia Livia; Miranti Putri Darmawanti (Universitas Muhammadiyah Magelang, 2023)
The degradation of dental hard tissues caused by the acidic activities of bacteria and fermentation, coupled with the disruption of the delicate balance between demineralization and remineralization processes, leads to the formation of cavities known as dental caries. The elevated prevalence of dental caries among children can be attributed to poor oral hygiene practices. This situation arises partly due to improper tooth brushing routines and a preference for consuming cariogenic foods. Educational efforts have been undertaken to address proper tooth brushing techniques, promote a non-cariogenic diet that includes an increased intake of fiber-rich fruits and vegetables, and provide education on hand hygiene as well as regular visits to the dentist every six months. The primary objective of these endeavors is to enhance children's knowledge and awareness of maintaining oral and dental health, with the ultimate goal of reducing the incidence of caries among children. After counseling, it was found that children's knowledge regarding dental health increased by 26.23%.